Development of Test Instruments Using Computer Based Test (CBT) Beesmart in the Evaluation of Aqidah Akhlak Learning at Islamic Senior High Schools in Topoyo, Central Mamuju Regency - Ma’sum; Hamdanah; Marhani; Muhdin; Buhaerah (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to develop a computer-based test instrument, the Beesmart Computer-Based Test (CBT) in evaluating Aqidah Akhlak learning at Madrasah Aliyah DDI Topoyo, Central Mamuju Regency. The research method uses the Research and Development development method with the ADDIE model including: 1) Analysis stage, (2) Design stage, (3) Development stage, (4) Implementation stage, (5) Evaluation stage. The results of this research show that: 1) the test instrument developed meets the criteria of being valid, reliable and practical to use. 2) The level of validity of data analysis from material experts is 85.55%, media experts are 90%, each with the category "very valid" . 3) The level of practicality obtained by the teacher response test analysis was 93.75% with the very interesting category. The small group student response was 91.66% with the very interesting category. And the response from a large group of students was 92.43% with the very interesting category. 4) The effectiveness test results obtained from the students' pretest and posttest showed an average score of 66.45. Meanwhile, the posttest results showed an average value of 86.62. In the t test, the Asymp value. Sig (2-tailed) = 0.000 < 0.05 indicates there is a difference.